Severe Bacterial Superinfection Based on Influenza A (H1N1) Pneumonia in a Heart–Lung Transplant Recipient - Yildirim, Y.; Pecha, S.; Sill, B.; Deuse, T.; Reichenspurner, H. (The Thoracic and Cardiovascular Surgeon, 2013)
A 47-year-old heart–lung transplant recipient presented to our outpatient transplant clinic with respiratory infection. Her nose and throat swabs for influenza A (H1N1) infection were negative. Broncheoalveolar lavage showed a positive result for H1N1 infection. Antiviral therapy was initiated. Because of superinfection with Pseudomonas aeruginosa and Aspergillus terreus, her clinical condition worsened. The clinical condition of the patient improved with antibiotic and antifungal treatment. Negative nose and throat swab results cannot rule out H1N1 infection safely. We therefore advocate to routinely perform broncheoalveolar lavage.
Keywords: infection; transplantation; heart–lung; cardiac